Cost-effectiveness of telerehabilitation versus traditional care after total hip replacement: A trial-based economic evaluation. (July 2021) - Nelson, Mark; Russell, Trevor; Crossley, Kay; Bourke, Michael; McPhail, Steven
Introduction: Physical rehabilitation for total hip replacement patients following hospital discharge is beneficial; however, accessing rehabilitation is often challenging. Telerehabilitation helps negate access issues and is efficacious in total knee and hip replacement patients. This study aims to compare the cost-effectiveness of a telerehabilitation programme delivered remotely into patients' homes versus traditional care for total hip replacement patients following hospital discharge. Methods: A cost-effectiveness (cost-utility) analysis was conducted from the perspective of a health service alongside a two-arm randomised controlled trial comparing telerehabilitation ( n =35) with in-person care ( n =35) following hospital discharge after total hip replacement. The primary analysis used an Incremental Cost-Effectiveness Ratio to compare the cost per Quality Adjusted Life Year (QALY) accrued in the telerehabilitation group versus in-person control using costs and effects data from the randomised trial. A secondary analysis was conducted whereby the time accrued by patients attending rehabilitation sessions (including travel time) was considered the "cost" (i.e. a time burden), rather than cost from the health service perspective. Results: Estimated mean differences in healthcare costs and QALYs gained were detected but were not significant. The estimated mean (95%CI) difference in cost of telerehabilitation versus in-person was –$28.90 (–$96.37 to $40.45), favouring the telerehabilitation group. The estimated mean (95%CI) difference in QALYs gained from telerehabilitation versus in-person was –0.0025 (–0.0227 to 0.0217). The estimated mean (95%CI) difference in time burden favoured less time burden for the telerehabilitation group (–4.21 (–4.69 to –3.74) hours). Discussion: Telerehabilitation in the total hip replacement population incurred similar costs and yielded similar effects to traditional in-person care. Telerehabilitation significantly reduced the time burden for patients and carers. These findings are valuable for healthcare providers seeking to implement accessible patient-centred rehabilitation services.